The Nixon Administration and the Middle East peace process, 1969-1973 : from the Rogers Plan to the outbreak of the Yom Kippur War - Vanetik, Boaz.; Shalom, Zaki.; Solomon, Guy. (Brighton : Sussex Academic Press, 2013)
The Yom Kippur War was a watershed moment in Israeli society and a national trauma whose wounds have yet to heal some four decades later. In the years following the war many studies addressed the internal and international political background prior to the war, attempting to determine causes and steps by political players and parties in Israel, Egypt and the United States. But to date there has been no comprehensive study based on archival materials and other primary sources. Classified documents from that period have recently become available and it is now possible to examine in depth a crucial period in Middle East history generally and Israeli history in particular. The authors provide a penetrating and insightful viewpoint on the question that lies at the heart of the Israeli polity and military: Was an opportunity missed to prevent the outbreak of the Yom Kippur War? The book provides surprising answers to longstanding issues:? How did National Security Adviser, Henry Kissinger, succeed in torpedoing the efforts of the State Department to bring about an interim agreement between Israel and Egypt in 1971?? Would that agreement have allowed Israel to hold on to most of the Sinai Peninsula for many years and at the same time avert the outbreak of the war.? Did Golda Meir reject any diplomatic initiative that came up for discussion in the years preceding the war?? Was the White House's Middle East policy throughout 1973 a catalyst for war breaking out?
Part 1. The twilight of the Nasser Regime: 1967-1970 -- The Middle East arena following the Six Day War -- The Johnson Administration's attempts to promote a settlement between Israel and Egypt in 1968 -- The "two-power talks" (US-USSR): March-September 1969 -- The First Rogers Plan, October-December 1969 -- The Rogers initiative for a ceasefire in the Suez Canal, June 1970, part 1 -- The Rogers initiative for a ceasefire in the Suez Canal, June 1970, part 2 -- The crisis in Jordan (September 1970) and its implications -- Part 2. "The stalemate policy": 1971-1972 -- Sadat replaces Nasser, Cairo and Washington begin moving closer -- Attempts to arrange an interim agreement in the Suez Canal: February 1971 -- Ongoing efforts to reach an interim Israeli-Egyptian agreement -- The unofficial death of the Rogers Plan -- Part 3. The run up to the Yom Kippur War: Autumn 1972-October 1973 -- Reinforcing the status quo in the region -- Complacency in the shadow of continued diplomatic stalemate -- Summary and conclusions.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Israel-Arab War, 1973 -- Causes; United States -- Foreign relations -- Israel; Israel -- Foreign relations -- United States; United States -- Foreign relations -- Egypt; Egypt -- Foreign relations -- United States; United States -- Foreign relations -- 1969-1974.; Guerre israélo-arabe, 1973 -- Causes; États-Unis -- Relations extérieures -- Israël.; Israël -- Relations extérieures -- États-Unis.; États-Unis -- Relations extérieures -- Égypte.; Égypte -- Relations extérieures -- États-Unis.; États-Unis -- Relations extérieures -- 1969-1974.; HISTORY -- Middle East -- General; Diplomatic relations; War -- Causes; Egypt; Israel; United States; 1969-1974